Rcompadre and Rage—Two R packages to facilitate the use of the COMPADRE and COMADRE databases and calculation of life‐history traits from matrix population models. Issue 4 (20th January 2022) - Jones, Owen R.; Barks, Patrick; Stott, Iain; James, Tamora D.; Levin, Sam; Petry, William K.; Capdevila, Pol; Che‐Castaldo, Judy; Jackson, John; Römer, Gesa; Schuette, Caroline; Thomas, Chelsea C.; et al.
Abstract: Matrix population models (MPMs) are an important tool for biologists seeking to understand the causes and consequences of variation in vital rates (e.g. survival, reproduction) across life cycles. Empirical MPMs describe the age‐ or stage‐structured demography of organisms and usually represent the life history of a population during a particular time frame at a specific geographical location. The COMPADRE Plant Matrix Database and COMADRE Animal Matrix Database are the most extensive resources for MPM data, collectively containing >12, 000 individual projection matrices for >1, 100 species globally. Although these databases represent an unparalleled resource for researchers, land managers and educators, the current computational tools available to answer questions with MPMs impose significant barriers to potential COM(P)ADRE database users by requiring advanced knowledge to handle diverse data structures and program custom analysis functions. To close this knowledge gap, we present two interrelated R packages designed to (a) facilitate the use of these databases by providing functions to acquire, quality control and manage both the MPM data contained in COMPADRE and COMADRE, and a user's own MPM data (Rcompadre ) and (b) present a range of functions to calculate life‐history traits from MPMs in support of ecological and evolutionary analyses (Rage ) . We provide examples to illustrate the use of both. Rcompadre and Rage will facilitate demographic analyses using MPM data and contribute to the improved replicability of studies using these data. We hope that this new functionality will allow researchers, land managers and educators to unlock the potential behind the thousands of MPMs and ancillary metadata stored in the COMPADRE and COMADRE matrix databases, and in their own MPM data. Resumen: Los modelos matriciales de población (MMPs) son una herramienta importante para aquellos biólogos interesados en comprender las causas y consecuencias de la variación de las tasas vitales (p.ej. supervivencia, reproducción) durante el ciclo de vida de las especies. Los MMPs empíricos describen la demografía de los organismos según su estructura de edades y/o estadios y suelen representar la historia de vida de una población durante un período de tiempo y en una localidad geográfica específica. Las bases de datos de MMPs de plantas COMPADRE y animales COMADRE son las que contienen una mayor cantidad de MMPs, las cuales, conjuntamente, contienen >12, 000 MPMs para >1, 100 especies a nivel mundial. Aunque estas bases de datos representan un recurso sin precedentes para investigadores, gestores medioambientales y educadores, las herramientas computacionales disponibles para contestar preguntas utilizando MMPs imponen barreras significativas a los potenciales usuarios, dado que requieren un conocimiento avanzado del uso de distintas estructuras de datos y lenguajes de programación para los análisis. Para cerrar esta brecha de conocimiento, presentamos dos paquetes de R interrelacionados diseñados para (a) facilitar el uso de estas bases de datos, proporcionando funciones para adquirir, controlar la calidad y manipular los datos de MMPs contenidas en COMPADRE y COMADRE, como los datos de MMPs propios de un usuario (Rcompadre ) y (b) presentar una serie de funciones para calcular atributos de la historia de vida de las especies a partir de dichos MMPs para análisis ecológicos y evolutivos (Rage ). Proporcionamos viñetas para ilustrar el uso de ambos paquetes. Rcompadre y Rage facilitarán los análisis demográficos utilizando datos de MMPs y contribuirán a mejorar la replicabilidad de los estudios que utilizan estos datos. Esperamos que esta nueva funcionalidad permita a los investigadores, gestores y educadores explotar el potencial que hay detrás de los miles de MMPs y los metadatos de las bases de datos COMPADRE y COMADRE, y en sus propios datos de MPM.